Comparing the Independent and Aggregated Accuracy of Trial 1 and the First 10 TOMM Items for Detecting Invalid Neuropsychological Test Performance Across Civilian and Veteran Clinical Samples. Issue 2 (April 2022) - Soble, Jason R.; Cerny, Brian M.; Ovsiew, Gabriel P.; Rhoads, Tasha; Reynolds, Tristan P.; Sharp, Dillion W.; Jennette, Kyle J.; Marceaux, Janice C.; O'Rourke, Justin J. F.; Critchfield, Edan A.; Resch, Zachary J.
Previous studies support using two abbreviated tests of the Test of Memory Malingering (TOMM), including (a) Trial 1 (T1) and (b) the number of errors on the first 10 items of T1 (T1e10), as performance validity tests (PVTs). In this study, we examined the independent and aggregated predictive utility of TOMM T1 and T1e10 for identifying invalid neuropsychological test performance across two clinical samples. We employed cross-sectional research to examine two independent and demographically diverse mixed samples of military veterans and civilians (VA = 108; academic medical center = 234) of patients who underwent neuropsychological evaluations. We determined validity groups by patient performance on four independent criterion PVTs. We established concordances between passing/failing the TOMM T1e10 and T1, followed by logistic regression to determine individual and aggregated accuracy of T1e10 and T1 for predicting validity group membership. Concordance between passing T1e10 and T1 was high, as was overall validity (87–98%) across samples. By contrast, T1e10 failure was more highly concordant with T1 failure (69–77%) than with overall invalidity status (59–60%) per criterion PVTs, whereas T1 failure was more highly concordant with invalidity status (72–88%) per criterion PVTs. Logistic regression analyses demonstrated similar results, with T1 accounting for more variance than T1e10. However, combining T1e10 and T1 accounted for the most variance of any model, with T1e10 and T1 each emerging as significant predictors. TOMM T1 and, to a lesser extent, T1e10 were significant predictors of independent criterion-derived validity status across two distinct clinical samples, but they did not offer improved classification accuracy when aggregated.